Evaluation And Comparison Of The Configuration Potential Energy Calculation For Be-Atom In Position Space - AL-Sharaa, Mayada J. ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
In the present work studies the theoretically the potential energy expectation value 〈V〉 for beryllium atom and like ions for different excited states ( , ( ) (where Z = 4. 13) and calculate the difference between each state to the same level , was used in this study wave function Hartree – Fook and the results contained in this search match with the published results of Hartree – Fook in 2003 (source 25) . been taking values of (n = 4, 5) to the( state and (n = 2, 3) of the ( ) state . The computer system Mathcad (Ver 2001i) is used in the present calculations after designing the required program.